İlhanlı Tarihine Ait Yeni Bir Kaynak: Tarih-i Vassf'ın Müellif Nüshası - (:unkn) unknown (My University, 2006)
0

Researchers in the field of medieval Iranian history know the importance of studies on the political and socio-economic history ofWassaf. There is also no doubt that they appreciate the difficulty of working with this valuable source. Sharaf al-Dln (or Shihâb al-Din) 'Abdallah b. 'Izz al-Din Fazlallâh Yazdi (Kâtib-i Shirâzı) wrote a five-volume work called Tajziyat a 1-amsar wa tazjıyat al-a 'sâr between the years 697/1298 and 728/1328. The fourth volume of the original autograph manuscript, completed at the end of the month Sha'bân, 711 (1-10 January 1312) is in the Nuruosmaniye Library (no. 3207), Istanbul. It is noteworthy that there is a kufic seal on the manuscript. The seal is exactly the same as that found on the manuscript in the Paris Bibliotheque Nationale (Persan 121) discovered by Prof. Francis Richard. The seal has been deciphered as having the inscription Vaqf-i Kitâbkhâııa-yi RashîdL This shows that the manuscript was for some time in the Rab'-i Rashidi Library in Tabriz. The presence of Turkish and Mongolian names in the Wassaf s autograph manuscript greatly helps in solving problems caused by4inguistic difficulties and scribal errors.
A New Source of Ilkhanid History: The Autograph Manuscript of Tarikh-i Wassaf
Keywords: Tarih